PHOTOMETRIC OBSERVATIONS OF A NEW ECLIPSING BINARY NSVS 8213217 - Udovichenko, S. N. (Одеські астрономічні публікації, 2016)
The photometric CCD observations for new suspected eclipsing binary NSVS8213217 inAstronomical stations nearOdessa(Ukraine) have been carried out. The light curves in V system were obtained and new adjusting period and light element was received. This star is identified as Algol-type eclipsing binary EA.